Regulation of the human cathepsin E gene by the constitutive androstane receptor - Page, Jeanine L. (2007)
Cathepsin E (CTSE) is an aspartic protease that has been linked to antigen processing and innate immunity. Elevated levels of CTSE expression have also been associated with several forms of cancer, including carcinomas exhibiting highly invasive character. In this study, we performed DNA microarray experiments, together with quantitative reverse transcriptase PCR analyses and enzymatic activity determinations to identify human CTSE as a novel target gene for regulation by the constitutive androstane receptor (CAR), a nuclear receptor activated by the liver tumor promoting agent, phenobarbital. In particular, two motifs within the 5′-flanking region of the human CTSE gene were identified as direct sites of interaction with CAR/RXRα heterodimers, a direct repeat-3 site at position −766 and a direct repeat-4 site at position −1407. Thus, these studies demonstrate CAR-mediated regulation of CTSE within primary hepatocyte cultures from several individual donors and suggest that elevated CTSE activity may play a functional role in the etiology of hepatocarcinogenesis.